Directly catalytic reduction of NO without NH3 by single atom iron catalyst: A DFT calculation. (1st May 2019) - Yang, Weijie; Gao, Zhengyang; Liu, Xiaoshuo; Ma, Chuanzhi; Ding, Xunlei; Yan, Weiping
Graphical abstract: Highlights: Single atom iron catalyst for directly catalytic reduction of NO without NH3 injection. L-H is the dominant reaction mechanism for the catalytic reduction of NO. The catalytic reduction of NO is exothermic and thermodynamically favorable. Abstract: Nitric oxide (NO) has been recognized as a major air pollutant, and the emission of NO has been strictly regulated. The technology of selective catalytic reduction of NO with NH3 injection is mature and efficient, but it still has some obvious drawbacks such as ammonia slipping, secondary fine particulates formation, and equipment corrosion. Therefore, a directly catalytic reduction of NO without ammonia injection by monovacancy graphene-based single atom iron catalyst (Fe/MG) was proposed. The detailed reaction mechanism was investigated through density functional theory calculation. Based on thermodynamic and kinetic analysis, we concluded that Langmuir-Hinshelwood is the dominant reaction mechanism for NO reduction, and the activation energy is 0.81 eV which is lower than char edges. The catalytic reduction reaction of NO is exothermic and thermodynamically favorable. The temperature can accelerate the catalytic reduction of NO. Based on the thermodynamic and kinetic performances of Fe/MG in NO reduction, Fe/MG is suggested to be a novel catalyst for NO reduction without NH3 . This theoretical research results can provide a new insight for NO removal and lay some foundations for subsequent experimental research.